2014
DOI: 10.1093/annonc/mdu230
|View full text |Cite
|
Sign up to set email alerts
|

Clinical activity of FOLFIRI plus cetuximab according to extended gene mutation status by next-generation sequencing: findings from the CAPRI-GOIM trial

Abstract: This study demonstrates that NGS analysis in mCRC is feasible, reveals high level of intra and intertumor heterogeneity, and identifies patients that might benefit of FOLFIRI plus cetuximab treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
108
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(115 citation statements)
references
References 16 publications
4
108
2
1
Order By: Relevance
“…One possibility is cancer intrinsic genetic heterogeneity, which could be more prominent in the metastatic setting (28,29). Heterogeneous genetic alterations in genes involved in the EGFR pathways have been hypothesized to play a role in resistance to anti-EGFR drugs in colorectal cancer, including activating mutations in KRAS, NRAS, B-RAF, and PIK3CA, and loss of expression of PTEN (13). The overall scenario is complicated by presence of additional genetic mechanisms able to activate the RAS pathway in the absence of molecular alterations affecting RAS or its immediate downstream effectors (30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is cancer intrinsic genetic heterogeneity, which could be more prominent in the metastatic setting (28,29). Heterogeneous genetic alterations in genes involved in the EGFR pathways have been hypothesized to play a role in resistance to anti-EGFR drugs in colorectal cancer, including activating mutations in KRAS, NRAS, B-RAF, and PIK3CA, and loss of expression of PTEN (13). The overall scenario is complicated by presence of additional genetic mechanisms able to activate the RAS pathway in the absence of molecular alterations affecting RAS or its immediate downstream effectors (30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular heterogeneity also plays an important role in the context of resistance, by limiting the success of therapies against a single target. Colorectal cancer patients can harbor different gene mutations in distinct tumor lesions, or even within different regions of the same lesion (13). All these alterations could converge on activation of the RAS-MEK-ERK pathway (9,10,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials have provided evidence that these mutations are negative predictors of response to anti-EGFR therapy [83][84][85][86][87][88]. BRAF is an immediate downstream molecule of RAS.…”
Section: Extended Ras and Braf Mutational Analysis For Metastatic Crcmentioning
confidence: 99%
“…Furthermore, the higher sensitivity of NGS may permit the identification of mutations in RAS not identified by the standard Sanger sequencing technique, as highlighted by the analysis conducted in a subpopulation of the CAPRI-GOIM multicenter study (13,14). In this regard, it was also suggested that low levels of KRAS mutations could justify an intrinsic resistance mechanism to anti-EGFR mAbs (15,16).…”
Section: Introductionmentioning
confidence: 99%